1998
DOI: 10.1007/bf02461640
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for studying science-in-the-making in educational settings

Abstract: In this paper we explore the methodological implications of sociocultural approaches for the study of scientific knowledge and practices. Research in science studies and science education is reviewed with a focus on methodological considerations. Informed by empirically-based studies of scientific practices from multiple disciplinary perspectives, we describe our perspective for investigating science education which combines ethnography and discourse analysis. This theoretical position on the discursive nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 39 publications
2
47
0
2
Order By: Relevance
“…Kelly in particular has argued that the focus of research should be on students' sensemaking practices, either through traditional or inquiry-oriented instruction (Kelly, Chen, & Crawford, 1998;Kelly & Duschl, 2002). Certainly, the development of certain practices that can be labeled as scientific is a main goal of recent reforms.…”
Section: Epistemology As Seen Through Practicementioning
confidence: 99%
“…Kelly in particular has argued that the focus of research should be on students' sensemaking practices, either through traditional or inquiry-oriented instruction (Kelly, Chen, & Crawford, 1998;Kelly & Duschl, 2002). Certainly, the development of certain practices that can be labeled as scientific is a main goal of recent reforms.…”
Section: Epistemology As Seen Through Practicementioning
confidence: 99%
“…Hirst (1974) wrote that learning a new concept is about using it, not about learning true conceptual relationships: BLearning a concept is like learning to play tennis, not like learning to state the rules and principles that govern play^(p. 125). This strengthens the argument for inquiry-based learning, not because it will necessarily produce better written test outcomes, but because it considers the empirical fact that concepts gain and change meaning through use, which is also true for science students (Lemke 1990;Kelly et al 1998;Wickman and Östman 2002a). An example from higher education is how Kelly et al (2000) showed how college students in an oceanography class productively learned epistemology and conceptual subject matter through practice alongside scientists, rather than through stipulated definitions.…”
Section: Genes and Experimental Practicementioning
confidence: 52%
“…En esta perspectiva el aprendizaje se entiende como un proceso cultural y discursivo (Leach y Scott, 2003). Los procesos discursivos se consideran como herramientas culturales utilizadas por los miembros de una comunidad determinada para construir el conocimiento (Kelly, Chen y Crawford, 1998).…”
Section: Procesos De Contextualizaciónunclassified